2022
DOI: 10.1002/hpm.3449
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice survey towards COVID‐19 vaccination: A mediation analysis

Abstract: Background and Aim The COVID‐19 pandemic has significantly impacted human lives across the world. In a country like India, with the second highest population in the world, impact of COVID‐19 has been diverse and multidimensional. Under such circumstances, vaccination against COVID‐19 infection is claimed to be one of the major solutions to contain the pandemic. Understanding of Knowledge, Attitude and Practice (KAP) measures are essential prerequisites to design suitable intervention programs. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…Sengupta et al did a similar study and mainly highlighted the attitude on COVID-19 vaccine, which will indirectly impact knowledge and practice. 6 In this study females (61.66%) were involved a higher percentage which was similar to the study done by Bhartiya et al 9 In the current study maximum involvement among students, second years MBBS 89 (29.6%) which is not similar to the study done by Vanathy et al showed third-year students 247 (61.8%). 10 The second-year students show high-grade knowledge 32 (36%) and they also had 42.7% of positive attitude and only 31.5% good practice.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Sengupta et al did a similar study and mainly highlighted the attitude on COVID-19 vaccine, which will indirectly impact knowledge and practice. 6 In this study females (61.66%) were involved a higher percentage which was similar to the study done by Bhartiya et al 9 In the current study maximum involvement among students, second years MBBS 89 (29.6%) which is not similar to the study done by Vanathy et al showed third-year students 247 (61.8%). 10 The second-year students show high-grade knowledge 32 (36%) and they also had 42.7% of positive attitude and only 31.5% good practice.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, a vaccine awareness campaign is done against the turbulence of anti-vaccination sentiments who are not willing to get vaccinated. 6 For any successful program, the most important criteria are vaccine acceptability. But many anti-vaccine movements and false beliefs among people are not getting vaccinated especially those with low socioeconomic status.…”
mentioning
confidence: 99%
“…In this study, the finding concurred with the theory that knowledge of COVID-19 was positively associated with vaccination intention. Similarly, Sengupta et al also demonstrated that knowledge of COVID-19 directly impacted the attitude and intention toward vaccination among the general public of India [38] .…”
Section: Discussionmentioning
confidence: 91%
“…It is advised that every immunization program must be trustworthy to be effective [ 40 ]. Additionally, it is equally important that the officials ensure vaccination dosages are secure, have judicious vaccine administration and effective management, and convince the general public of vaccines’ safety and effectiveness while inspiring them to accept them [ 7 , 40 ]. Maternal IgG can pass through the placenta and give the newborn immunity [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main intermediary between pre-existing information and actual COVID-19 immunization practice can be attitude [ 40 ]. These results are the foundation of public health awareness campaigns that must work to change people’s attitudes in a favorable direction [ 40 ].…”
Section: Discussionmentioning
confidence: 99%